Efficacy and Tolerability of Methotrexate versus Azathioprine in the Treatment of Chronic Actinic Dermatitis - Basri, Rabia; Inayat, Sara; Zafar, Summaya; Jahangir, Sundus; Sajida; Majeed, Somia (Indus Journal of Bioscience Research, 2025)
Background: Chronic actinic dermatitis causes persistent, itchy plaques in sun-exposed areas; systemic treatments are used, but comparative data remain limited. Objective: to evaluate methotrexate’s and azathioprine’s effectiveness and tolerability in treating chronic actinic dermatitis, with an emphasis on symptom relief, photosensitivity reduction, side effects, patient satisfaction, and treatment compliance. Methodology: This six-month qualitative study was carried out at a Quetta tertiary care facility. Purposively sampled, 200 adult patients with moderate-to-severe CAD who were not responding to topical therapy were split into two groups: 100 were given azathioprine and 100 were given methotrexate. Through patient interviews, medical records, and clinical examinations, clinical outcomes, side effects, and patient-reported improvements were evaluated. Thematic content analysis was used for analysis. Results: 72% of methotrexate patients reported a significant improvement, compared to 65% in the azathioprine group. Clinical results showed that methotrexate was superior, with shorter time to respond (4–6 weeks vs. 6–8 weeks), higher reductions in skin lesions (85% vs. 78%), increases in quality of life (82% vs. 76%), and decreased photosensitivity (80% vs. 75%). While azathioprine induced more gastrointestinal distress (20% vs. 12%), methotrexate was linked to higher levels of nausea (22% vs. 18%) and increased liver enzymes (10% vs. 8%). The methotrexate group had somewhat greater patient satisfaction and adherence rates (70% highly satisfied; 88% adherence) than the azathioprine group (62% highly satisfied; 85% adherence). Conclusion: Methotrexate offers quicker relief and higher satisfaction in CAD, but both drugs are effective; azathioprine suits methotrexate-intolerant patients.